Capacidad de autocuidado en pacientes que asisten al programa de Diálisis peritoneal ambulatoria continua del Hospital ii Essalud Tarapoto Junio- Setiembre de 2012 - Acuña García, Paolo Cesar (2012)
The patients that receive peritoneal dialysis, should change their lifestyle to survive, learning and carrying out activities to take care of if same, with the modifications that it imposes him the illness; everything will allow him to it to feel well, to stay independently in their social, labor and family environment. The success of this therapy will depend on the self care capacity that they have to develop activities of the daily life and the goods that it imposes him the illness; being it an area that requires of valuation and orientation of the self care. It is so the present investigation had for objective to determine the self care capacity in the patients that receive peritoneal dialysis, taking like mark reference to the general Theory of autocuidado of Dorothea Orem. The study is descriptive of cross section, carried out in 32 patients that receive peritoneal dialysis in the EsSalud II Hospital of Tarapoto, selected by sampling non probabilistic. It was used like instrument: The Valuation of self care Capacity. Which was classified in: high, half and under. Use of the software SPSS version was not made 15.0. The results were: in the self care capacity 50% shows high level, 37.5% it presents half level and the 12.5 % it presents low level, in the abilities to carry out the activities of the daily life 69% shows a high level, 19% it presents a half level and 12% a low level and in knowledge to carry out self care activities in front of the illness 47% shows high level, 28% a low level, and 25% a low level, being concluded that the patients evidenced a high-level of self care capacity; in front of the activities of the daily life and in knowledge to make in front of the illness.